(untitled) (Eurasian Journal of Philology Science and Education, 2015)
The article investigates lexical-stylistic layers of language on the basis of poeticisms, archaisms, barbarisms, terms, vulgarisms, colloquial everyday words, etc. Two styles function in the language: spoken colloquial style and written bookish style. Each style has its own lexical means of expression. Colloquial language is a daily means of communication requiring the use of clear words. Communication is based on the basis of dialogue, without special preparation, it is accompanied by facial expressions and gestures, it is expressive and emotional. Therefore in such communication interlocutors don’t think of the accurate choice of lexical means and correct grammatical form of expression.